Mandela : the authorised biography - Sampson, Anthony, 1926-2004.; Battersby, John D. (London : HarperPress, 2011)
Widely considered to be the most important biography of Nelson Mandela, Antony Sampson's remarkable book has now been updated by acclaimed South African journalist, John Battersby. Over a decade after his presidency of South Africa, Nelson Mandela remains an inspirational figure to millions of people -- both in his homeland and far beyond her borders. He is, without doubt, one of the most important figures in global history. Mandela's opposition to apartheid and his 27 year incarceration at the hands of South Africa's all-white regime are familiar to most. In this utterly compelling book, eminent biographer Anthony Sampson, who knew his subject since 1951, reveals the man behind the events that rocked a continent -- and changed the world.
Previous ed: 1999.
Includes bibliographical references and index.
Keywords: Mandela, Nelson, -- 1918-2013.; Mandela, Nelson, -- 1918-2013.; Presidents -- South Africa -- Biography; Presidents; South Africa; Biography